Correlates of malnutrition in patients with heart failure: the role of social support - Mohammad Hossein Sharifi; Maryam Afshari; Hossein Molavi Vardanjani; Amirreza Nikmanesh; Mohammad Hossein Nikoo (ESC Heart Failure, 2024)
Abstract Aims Heart failure (HF) is a major public health challenge. Malnutrition has a significant effect on HF prognosis. Understanding the impact of social and clinical factors on the risk of malnutrition is necessary because it may aid in improving the health status of HF patients. Methods and results Three hundred twenty patients with HF who were hospitalized in a heart centre in Shiraz, Iran, from March to November 2022 were studied. Two validated questionnaires were used to evaluate malnutrition and social support: (1) Mini‐Nutritional Assessment Short Form and (2) Medical Outcomes Study Social Support Survey. The participants were then divided into three groups: those with normal nutritional status (scores 12–14), those at risk of malnutrition (scores 7–11), and those who were malnourished (scores 0–6). The potential correlates of malnutrition (including socio‐demographic, clinical, comorbidities, and laboratory factors) were included in the study. Then, ordinal logistic regression was used to investigate the correlates of malnutrition. The mean age of the participants was 64.2 ± 11.2 years, and more than half were male and married. Normal nutritional status was seen in 110 (34.4%) participants, 151 (47.2%) were at risk of malnutrition, and 58 (18.1%) were malnourished. The mean social support score of the participants was 61.65 ± 12.91. According to the adjusted odds ratios (95% confidence intervals) obtained from multivariate analysis, increased risk of malnutrition was associated with having a lower social support score [0.95 (0.93–0.97), P‐value ≤ 0.001], lower body mass index [0.91 (0.86–0.97), P‐value = 0.004], higher New York Heart Association classification [1.26 (1.02–1.56), P‐value = 0.03], longer duration of disease [1.006 (1.001–1.01), P‐value = 0.006], and lower serum albumin level [0.25 (0.08–0.75), P‐value = 0.01]. Conclusions Besides the clinical conditions affecting the risk of malnutrition in patients with HF, social support may play an important role. Including this factor in HF guidelines and developing educational programmes may help improve HF patients' health.